EFFECTIVENESS OF MIRROR THERAPY ON MUSCLE STRENGTH IMPROVEMENT AND ANXIETY REDUCTION IN STROKE PATIENTS: A QUASI-EXPERIMENTAL STUDY - Eko Budi Santoso; Podo Yuwono; Arnika Dwi Asti (Jurnal Kesehatan Kusuma Husada, 2026)
Background: Stroke is a leading cause of long-term disability. Muscle weakness and anxiety can impede rehabilitation outcomes and diminish quality of life. Mirror therapy is a low-cost intervention increasingly used in stroke rehabilitation; however, evidence regarding its combined effects on motoric and psychological outcomes remains limited.Methods: This quasi-experimental study used a pretest–posttest control group design with 52 subacute stroke patients randomly allocated to an intervention group (n=26) and a control group (n=26). The study was conducted at a hospital-based stroke rehabilitation center in Central Java, Indonesia, from March to June 2025. The intervention group received mirror therapy for 30 minutes per session, five times weekly for four weeks, alongside standard rehabilitation, whereas the control group received standard rehabilitation only. Muscle strength was assessed using the Medical Research Council (MRC) Scale, and anxiety was measured using the Hospital Anxiety and Depression Scale (HADS). Paired and independent t-tests were used for within- and between-group analyses.Results: The intervention group demonstrated significant improvements in muscle strength and significant reductions in anxiety scores across both posttest measurements (p<0.001). In contrast, the control group showed no significant changes (p>0.05). Post-intervention comparisons indicated significantly higher muscle strength and lower anxiety levels in the intervention group compared to the control group (p≤0.001).Conclusion: Mirror therapy effectively enhances muscle strength and reduces anxiety in subacute stroke patients. Its simplicity, low cost, and non-invasive nature support its integration into stroke rehabilitation programs, particularly in resource-limited settings.